Application of Upper Bound Analysis and Taguchi Method in Aluminium Extrusion - Kamardeen A. OGUNBAJO; Benjamin I. UGHEOKE; Ibrahim D. MUHAMMAD; Emmanuel ONCHE (FUDMA Journal of Engineering and Technology, 2025)
This research explores the use of upper bound analysis in calculating the extrusion force through u-shaped dies with varying fillet radii, billet lengths, friction coefficients and billet temperatures. Taguchi method was used in design of this experiment which is a four factor four level experiment giving a total of 16 experimental runs and aluminium 3003 was used as the workpiece. Based on these results a model equation was developed to predict the extrusion force. The correlation coefficient and covariance of the data generated, revealed that a positive and direct relationship  existed between fillet radius, billet length, friction coefficient and extrusion force, while an inverse and indirect relationship existed between billet temperature and extrusion force. The R2 value was 99.96% and adjusted R2 value of 99.80% and a root mean square error of 0.2137, indicating that the accuracy of the model is good.
Keywords: Billet lengths, billet temperatures, friction coefficients, fillet radii, Taguchi Method.